2017
DOI: 10.1140/epjh/e2016-70064-9
|View full text |Cite
|
Sign up to set email alerts
|

The history of research into improved confinement regimes

Abstract: Abstract. Increasing the pressure by additional heating of magnetically confined plasmas had the consequence that turbulent processes became more violent and plasma confinement degraded. Since this experience from the early 1980ies, fusion research was dominated by the search for confinement regimes with improved properties. It was a gratifying experience that toroidally confined plasmas are able to self-organise in such a way that turbulence diminishes, resulting in a confinement with good prospects to reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 106 publications
1
25
0
Order By: Relevance
“…Recent work has led to a merger, of sorts, between the two lines of research focusing on density limits and confinement transitions, as schematized in figure (1). In particular, two experimental studies have reported findings that link the decay of the ubiquitous edge shear layer (in L mode) and a concomitant increase in turbulent particle flux to the approach n/n G → 1.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has led to a merger, of sorts, between the two lines of research focusing on density limits and confinement transitions, as schematized in figure (1). In particular, two experimental studies have reported findings that link the decay of the ubiquitous edge shear layer (in L mode) and a concomitant increase in turbulent particle flux to the approach n/n G → 1.…”
Section: Introductionmentioning
confidence: 99%
“…Upon using in (6) the fact that the L-H transition occurs when Ploss,i > ∼ P L−H,i , the criterion on P L−H for the L-H transition becomes…”
Section: Phenomenological Model For the L-h Power Thresholdmentioning
confidence: 99%
“…Immediately after the H-mode discovery [1], a correlation between sawtooth crash and L-H transition was observed [5]: A heat wave which propagates towards the plasma edge is associated with the sawtooth crash, and because of the correlation between sawtooth crash and the formation of the ETB, the heat wave was thought to be the cause of the ETB formation [5]. At that time, however, it was not clear whether this heat wave was carried by all the plasma species, or only by one and which [6]. It became clear that ion-heat flux was the real responsible for the creation of the ETB, only when preciser measurements of the ion temperature were available and thanks to dedicated experiments with dominant ion heating, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The history of improved confinement regimes is narrated in Ref. 9, which also gives the most relevant references.…”
Section: Confinement Of High-temperature Fusion Plasmasmentioning
confidence: 99%